Kaum Miskin Kota, Sampah, dan Rumah: Studi tentang Akses Migran Miskin terhadap Sumber Daya Lingkungan dan Perumahan di Tangerang - Cahyadi, Rusli (UI Scholars Hub, 2011)
A slum or squatter is identified by poor quality of housing and unsanitary conditions. The common agreed explanation of the conditions is to link the rapid growth of population, poverty and environment limitations. It implies that, internal factors of the poor people was the major cause the environmental deteorization. This article is an attemp to explore another explanation. It argued that external factors, i.e. government polices, are the ultimate cause. Using the case of waste management and urban housing supply system, the article propose a different view. The poor and unsanitary housing was the result of lack and absence of city government programm on the place. Any local initiatives to manage waste and improve housing conditions will be bumped by the fact no local waste management system is connected to municipal waste management system. As an implication, this article offers a new perspective to the existence of slum and squatter. It must be seen as a necessity and an integral part of urban development.